Pemanfaatan Abu Cangkang Kopi Sebagai Substitusi Semen Untuk Bahan Beton Ringan Menggunakan Bahan Tambah Sikament NN - Kurnia, R Dedi Iman; Suhaimi; Ismy, Romaynoor; Akmal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Almuslim, 2024)
The chemical reaction of cement and water produces compounds that are alkaline and react with various acids so that they can reduce the quality of concrete. To minimize this effect, pozzolanic materials need to be added. Organic pozzolan materials such as coffee shell ash waste can be used as material for making lightweight foam concrete which can be applied to non-structural buildings such as lightweight bricks. This research was conducted to see the effect of coffee shell ash substitution for cement on the properties of fresh concrete and the mechanical properties of lightweight foam concrete and to find the most optimal substitution composition for coffee shell ash for cement as well as lightweight foam concrete with FAS 0.5. Substitution of coffee shell ash for cement weight was carried out with variations of 0% BBN, 5% BBAAK1, 10% BBAAK2, and 15% BBAAK3 using 1% superplasticizer additive. The test object used is a cylinder with dimensions of 15 cm x 30 cm. The number of test objects used was 24 pieces. Tests for compressive strength and split tensile strength were carried out at the age of 28 days. The results of compressive strength tests carried out at 28 days for the lightweight foam concrete variations BBN, BBAAK 1, BBAAK 2 and BBAAK 3 were respectively 15.29 MPa, 12.21 MPa, 18.29 MPa and 19.52 MPa. The greater showing variation in the percentage of coffee shell ash substitution used, the greater the resulting compressive strength and split tensile strength values. This is because Sikament NN also plays a role in increasing the compressive strength of concrete